Validation of reference transcripts in strawberry (Fragaria spp.) - Clancy, Maureen A. (2013)
Contemporary methods to assay gene expression depend on a stable set of reference transcripts for accurate quantitation. A lack of well-tested reference genes slows progress in characterizing gene expression in high-value specialty crops. In this study, a set of strawberry (Fragaria spp.) constitutively expressed reference genes has been identified by merging digital gene expression data with expression profiling. Constitutive reference candidates were validated using quantitative PCR and hybridization. Several transcripts have been identified that show improved stability across tissues relative to traditional reference transcripts. Results are similar between commercial octoploid strawberry and the diploid model. Our findings also show that while some never-before-used references are appropriate for most applications, even the most stable reference transcripts require careful assessment across the diverse tissues and fruit developmental states before being adopted as controls.